Parental Upward and Downward Mobility and Its Influence on Girls' Secondary Education and Women Empowerment: An Intergenerational Analysis in Muzaffarabad, AJ&K - Nafeesa Mir Zaman,; Dr. Amjad Reba,; Zubaida,; Dr. Shakeel Ahmed,; Muhammad Waseem, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the impact of parental upward and downward mobility on girls' secondary education and subsequent women’s empowerment in Muzaffarabad, Azad Jammu & Kashmir (AJ&K), utilizing an intergenerational lens. Through a qualitative, exploratory research design, the study explores how socio-economic shifts within families influence educational aspirations, career trajectories, and empowerment outcomes for girls. A purposive sample of 30 female students and 10 parents from two Governments Higher Secondary Schools (GHSS), one urban and one rural was selected. Data was gathered through semi-structured interviews with students and their parents, focusing on parental mobility, girls' educational outcomes, aspirations, and empowerment. Thematic analysis was employed to examine the data, identifying key themes related to mobility, geographical disparities in education, factors contributing to intergenerational mobility, and socio-economic status. The findings indicate that upward mobility significantly enhances girls' educational opportunities and empowerment, while downward mobility often limits access to quality education and socio-economic advancement. This research highlights the critical role of parental socio-economic status in shaping educational outcomes and the broader socio-cultural empowerment of women, emphasizing the need for targeted educational policies that address these disparities in Muzaffarabad, AJ&K. Keywords: Mobility, Empowerment, Intergenerational, Aspirations, Disparities, Socio-cultural, Upward Mobility, Downward Mobility